Petrology and U-Pb geochronology of a late-hercynian subalkaline granitic massif, NW Iberian Peninsula - Mendes, Anabela Carreira (1997)
Junta Nacional de Investigação Científica e Tecnológica. PRAXIS/2/2/CTA/391/94 Project. French Embassy Cooperation Programme.